Food addiction linked to changes in ventral striatum functional connectivity between fasting and satiety. (1st February 2019) - Contreras-Rodriguez, Oren; Burrows, Tracy; Pursey, Kirrilly M.; Stanwell, Peter; Parkes, Linden; Soriano-Mas, Carles; Verdejo-Garcia, Antonio
Abstract: Introduction: The concept of "food addiction" (FA) has gained popularity in view of clinical and neurobiological overlaps between excessive food intake and addictive disorders. However, no studies have examined the link between FA and striatocortical circuits involved in addictive disorders, or the influence of homeostatic status, which regulates the drive to eat, on these systems. This study aims to investigate changes in striatal functional connectivity between fasted and fed conditions among adults ranging in body mass index (BMI) and FA symptoms. Methods: Thirty adults were recruited from the general community and completed self-reported surveys including demographics, FA symptoms using the Yale Food Addiction Scale, as well as height and weight measures, used to determine BMI. Participants completed two 3-T MRI scans, one in a fasted state and one in a fed state. We conducted seed-based analyses to examine between-session ("fasted > fed") change in resting-state functional connectivity of the ventral and dorsal striatum, and its association with FA scores (controlling for BMI). Results: Higher symptoms of FA correlated with greater changes in ventral caudate-hippocampus connectivity between fasted and fed conditions. FA symptoms did not correlate with connectivity in the dorsal caudate circuit. Post-hoc analyses revealed that participants with higher symptoms of FA had ventral caudate-hippocampus hyperconnectivity in the fasted scan only, as well as a significant reduction of this connectivity between the fasted and fed scans. Conclusions: Heightened connectivity in the ventral striatum during a fasted state, which has been linked to reward prediction signals, underpins symptoms of FA. In contrast, connectivity in the dorsal striatum or "habit" system is unrelated to homeostatic status and FA symptoms, and is thus less relevant for subclinical manifestations of FA.